Revısiting the scattering regime map based on transport scattering coefficient - Taufiq, Aristo. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2023., 2023)
Radiative transfer in media consisting of randomly dispersed particles is commonly found in various scientific and engineering applications. The norm for analyzing such systems is to use the independent scattering assumption, where the radiative characteristics of the system are derived from the superposition of the individual particles’ radiative characteristics. One criterion for the validity of this assumption is that the particles are sparsely distributed. If this is not the case, estimation of properties for dependent scattering necessitates a more rigorous analysis. Historically, researchers have established regime maps that are used to identify if the independent scattering assumption is valid. However, recent experiments in the literature have shown that the well-established regime map may have shortcomings and predicts certain cases to be within the validity of the independent scattering assumption, although they are not. In this paper, a new regime map is sought considering the effect of particle refractive index. The study is established through numerical simulations using the static structure factor that accounts for the dependent scattering. The approach is validated with an experimentally verified method based on the T-matrix method, considering only the incoherent component of the scattered electric field, which represents the scattering of electromagnetic waves propagating through a dense medium. Coherent and incoherent coefficients were overlooked in recent studies, resulting in erroneous interpretations of the location of the demarcation line and the effect of the refractive index. To rectify this, the present study uses the transport scattering coefficient as a single intrinsic characteristic to define the transition between independent and dependent scattering. The transport scattering coefficient has been proven to correlate well with reflectance, unlike the scattering coefficient and the asymmetry parameter.
Keywords: Random walks (Mathematics); Mechanical engineering.